THE URGENCY OF RESCHEDULING POLICY AS A SOLUTION TO SHARIA BANKING DISPUTE ON MURABAHAH AGREEMENTS - Mohamad Hidayatullah A.K Husein; Abdul Mujib; Nenden Herawaty Suleman (Tasharruf: Journal Economics and Business of Islam, 2022)
The purpose of the study is to examine the rescheduling of Murabahah finance as an alternative to using dialogue as a means of resolving economic issues in Islamic banking. As a result, there will be reciprocal protection and legal clarity for both parties. Therefore, normative legal research will be used in this study because it offers secondary information in the form of secondary legal material by examining or studying the notion of law as a useful tool or norm in the legal system that regulates human existence. This study falls under the category of library research. The possibility of rescheduling murabahah funding contracts in terms of time and shared objectives is studied using secondary data. Results of research The urgency of the scheduling policy undoubtedly benefits both banks and customers. Banking solutions can be discovered to resolve difficult financing issues in Murabahah contracts by discussion and consensus to find a way out of these challenges by opening this policy space and changing the thinking of customers. The bank strengthens risk management and makes sure that Sharia law is followed when implementing every policy. But in this instance, improving and overseeing management is undoubtedly preferable. Consumers who have trouble completing payments are additionally given assistance, and customers are given instructions to help them avoid this issue in the future. as well as possibilities for consumers to collaboratively draft the terms of the agreement and make the murabahah contract's provisions clear to them.